Diagnostic and therapeutic implications of relationships between fasting, 2-hour postchallenge plasma glucose and hemoglobin A1c values - Woerle, Hans J.; Pimenta, Walkyria P.; Meyer, Christian; Gosmanov, Niyaz R.; Szoke, Ervin; Szombathy, Tamas; Mitrakou, Asimina; Gerich, John E. (American Medical Association (AMA), 2004)
Background: Increased fasting plasma glucose (FPG) and 2-hour postchallenge plasma glucose (PCPG) levels with normal hemoglobin A1c (HbA 1c) levels are recognized as risk factors for cardiovascular disease. We undertook this study to determine the relationships between FPG and 2-hour PCPG levels over the normal HbA1c range and to assess the need to control FPG and 2-hour PCPG levels to achieve HbA1c targets recommended by the American Diabetes Association (ADA), International Diabetes Federation (IDF), and American College of Endocrinology (ACE). Methods: The data of all healthy individuals with HbA1c values less than 7.0% (N=457) who underwent oral glucose tolerance tests between 1986 and 2002 for either screening as potential research volunteers (93%) or diagnostic purposes (7%) were analyzed. Results: Of 404 individuals with normal HbA1c levels (<6.0%), 60% had normal glucose tolerance, 33% had impaired glucose tolerance, 1% had isolated impaired FPG, and 6% had type 2 diabetes mellitus. Of 161 individuals without normal glucose tolerance, 80% had normal FPG levels. Both FPG and 2-hour PCPG levels increased as HbA1c increased and were significantly correlated (r=0.63, P<.001), but the 2-hour PCPG level increased at a rate 4 times greater than FPG and accounted for a greater proportion of HbA1c. People who met the IDF and ACE HbA1c targets (<6.5%) had significantly lower 2-hour PCPG levels than those who met the ADA target (<7.0%) (P=.03), whereas FPG levels were similar. Conclusions: Most individuals with HbA1c values between 6.0% and 7.0% have normal FPG levels but abnormal 2-hour PCPG levels, suggesting that an upper limit of normal for FPG at 110 mg/dL (6.11 mmol/L) is too high and that attempts to lower HbA1c in these individuals will require treatment preferentially directed at lowering postprandial glucose levels.